Development of the Story of Life: A Narrative and Educational Game Using the Godot Engine for Android - Kusheryanto, Andhika; Mirza, Anis; Syaripudin, Ari; Hutagalung, Deanna Durbin (JISA(Jurnal Informatika dan Sains), 2024)
Godot Engine, as an open-source platform, offers flexibility and ease of use for developing both entertaining and educational games. This research showcases the creation of Story of Life, an educational game aimed at engaging players in learning through interactive storytelling and character-driven quests. The game features a character named Ucup, who explores various environments, clearing questions, and interacts with NPCs to gain knowledge and complete learning-based challenges. The development process followed the Agile Software Development Life Cycle (SDLC), with rigorous testing conducted through black-box and white-box methodologies. Testing results indicate a 97% success rate in functionality and performance on low-spec devices, confirming the game’s compatibility and responsiveness. The findings demonstrate that Story of Life successfully combines narrative with educational content, providing a meaningful and accessible learning experience.